PENGARUH FINANCIAL LITERACY, OVERCONFIDENCE, REGRET AVERSION BIAS DAN RISK TOLERANCE TERHADAP INVESTMENT DECISION DI KOTA BATAM - IRA RAHMADANIA PUTRI; HIKMAH . (LP2MTBM MAKARIOZ, 2020)
Rise of the case of illegal investment in Batam City illustrates that the financial knowledge of investors and potential investorsis still not good. Even though financial literacy index in Batam has penetrated the national target, it cannot be used as areason why investors decide to invest. the number of investors who have high overconfidence makes many investors aredeceived by investment fraud in Batam City. Moreover, investors who have previously made mistakes in investing andexperiencing losses, a high sense of doubt will interfere with these investors in investing. Furthermore, investors in Batamhave various levels of tolerance to investment risk. The greater income of an investor in investing, the higher tolerance forfurther investment. Investment decisions that are only based on one factor are certainly not a good decision, because it isprone to mistakes in making decisions. The purpose of this study is to determine the partial and simultaneous influence offinancial literacy, overconfidence, regret aversion bias and risk tolerance variables on investment decisions in Batam City.This research is a quantitative study with a sampling technique using simple random sampling using Krejcie and Morgantables with a sample of 375 respondents. The analytical method used is multiple linear regression analysis and uses a Likertscale as a measurement scale. T-test results (partial test) states that the variables of financial literacy, overconfidence, regretaversion bias and risk tolerance partially have a positive and significant effect on investment decisions. And the results of theF test (simultaneous test) states that financial literacy, overconfidence, regret aversion bias and risk tolerance together havea positive and significant effect on investment decisions in Batam City. Data management tools used in this research is theapplication of SPSS version 22.